Evaluating AI-Based Digital Marketing Resources: A VRIO Framework Analysis for Competitive Advantage Assessment in Pre-Launch Skincare Brands - Setiawan, Joseph; Bryan Ciputra, Mikael; Sanjaya, Brianna; Antonius Felix, Antonius Felix (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – This study aims to evaluate the AI-enabled digital marketing resources of L’Essaine, a pre-launch skincare brand, using the VRIO (Value, Rarity, Imitability, and Organization) framework grounded in Resource-Based View (RBV) theory, in order to assess their potential to generate competitive advantage. Design/methodology/approach – Using a qualitative strategic analysis approach, this research applies the VRIO framework to identify and assess ten key AI-enabled and brand-related digital marketing resources of L’Essaine against the four VRIO criteria. Findings – The findings indicate that AIGC specialist expertise and AI-driven content capabilities provide a temporary competitive advantage, as these resources are valuable and relatively rare but are expected to become imitable within a 12–24 month timeframe. In contrast, the brand story and identity resource satisfies all VRIO dimensions, thereby constituting a source of sustainable competitive advantage. The remaining six resources are classified as providing competitive parity. Research limitations/implications – This study is limited by its qualitative nature and pre-launch context, as the analysis is based on strategic resource assessment rather than post-implementation performance outcomes. Future research could examine similar AI-enabled digital marketing resources in post-launch or multi-brand contexts to validate and extend the findings. Practical implications – From a strategic perspective, the results underscore the importance for firms to exploit short-term advantages derived from AI capabilities while concurrently investing in more enduring, brand-based resources. The study offers managerial insights into the strategic allocation of digital marketing resources to maximize competitive advantage in highly competitive industries. Originality/value – This study contributes to the strategic management and digital marketing literature by elucidating how AI technologies can generate differentiated value within the skincare industry. Its originality lies in integrating VRIO analysis with AI-enabled digital marketing resources in a pre-launch brand context, providing a structured approach to understanding how temporary and sustainable advantages can be strategically balanced.